Pelatihan Layanan Prima bagi Management Gedung Inalum Kuala Tanjung - Ruliyanta; Wismanto Setyadi (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2022)
The Inalum Building of Kuala Tanjung is the grandest building in Batubara Regency and is an icon for this district. Since it was inaugurated on January 6, 2021, by the minister of SOEs, the building has started operating. This building is the head office of PT Inalum (Persero), a well-known BUMN in Indonesia. By carrying out Smart and Green Building, Inalum's leadership has a high commitment to local hospitality values. In addition to buildings with modern architecture combined with Malay-style facades, the absorbed workforce also prioritizes residents. For this reason, the location for Community Service was chosen in this building because it aims to improve the capabilities and skills of the technicians in operating this building. For this reason, the theme of Electrical Distribution System Training in Buildings for Technicians of the Inalum Building of Kuala Tanjung, Batu Bara, North Sumatra. The training was carried out on December 4, 2021, with 45 participants. Hopefully, with this training, the National University can make a better contribution to the Indonesian people, especially in areas far from the national capital